Role of Arterial Blood Gas (ABG) as a valuable assessment tool of disease severity in SARS-CoV-2 patients - Amrita, Jyot; Singh, ArvinderPal (Journal of Medical Biochemistry, 2021)
Summary Background: COVID-19 is caused by a novel coronavirus, named severe acute respiratory syndrome coronavirus2 (SARS-CoV-2). The foremost predominant complication of SARS-CoV-2 is arterial hypoxemia thereby disturbing lung compliance, requiring mechanical ventilation. The aim of the current research study is to analyze role of ABG as a valuable assessment tool of disease severity in SARS-CoV-2 patients. Methods: 170 arterial blood samples were collected from patients admitted in Intensive Care Unit (ICU) of Sri Guru Ram Das Charitable Hospital, Amritsar. They were analyzed for arterial blood gas using ABG analyzer. Parameters of ABG such as pH, pCo2, HCO3, O2 saturation, ionized calcium (iCa) and calculated ionized calcium (at pH 7.4) was calculated for all the samples. Results: Continuous variables were described as medians with interquartile ranges (IQRs) and categorical variables as percentages and frequencies. Spearman correlation test was done for calculation of correlation between pH and other ABG parameters. Analysis of arterial blood gas revealed significant negative correlation (p<0.05) between pH and pCO2 and significant positive correlation (p<0.05) between pH and HCO3 and between pH and delta ionized calcium. Low levels (98.2%) of ionized calcium were observed while monitoring the ABG findings though weak negative correlation (p<0.05) was observed between pH and iCa. Conclusion: Our study suggests that ABG analysis acts as a momentous indicator for critically ill patients admitted in Intensive Care Unit (ICU). Estimation of iCa in this critical care setting acts as a distinctive biochemical feature of SARS-CoV-2 disease, as an initial assessment tool, for hypocalcemia. Keywords: Arterial Blood Gas, SARS-CoV-2, Ionized Calcium, Hypocalcemia